Strategi Pemasaran Rumah Sakit Pasca COVID-19 di Indonesia: Scoping Review - Deviriyanti Agung, Andi; Sulistiadi, Wachyu (Jurnal Etnik: Ekonomi-Teknik, 2023)
The COVID-19 pandemic has had a significant impact on the health services market in Indonesia, requiring the development of new and innovative marketing strategies. With mobility restrictions and limited access to healthcare facilities, healthcare companies must adapt to ensure patient needs are met. This study explores innovative marketing approaches being implemented in the healthcare sector, particularly considering the limitations caused by the pandemic. This study reveals a heavy reliance on internet and social media platforms to market healthcare products, reflecting a shift in strategies to meet changing consumer needs and behavior over time.